Influence of Sr2+ ion substitution on structural, morphological, optical, thermal, and magnetic behavior of MgFe2O4 cubic spinel. Issue 4 (10th December 2020) - Baskar, S; Yuvaraj, S; Partha Sarathi, Subudhi; Sundararajan, M; Chandra Sekhar, Dash
Abstract: Utilizing L‐arginine as a fuel, Mg1‐ x Sr x Fe2 O4 (0 ≤ x ≤ 0.5) spinel nanoparticles were prepared by the microwave combustion process. Impact of Sr 2+ ion substitution on structural, morphology, optical, thermal, and magnetic characteristics is investigated by following techniques such as X‐ray diffraction (XRD), HR‐SEM, energy dispersive X‐ray analysis (EDX), diffused reflectance spectroscopy‐Ultra Violet (DRS‐UV), TG‐DTA, and VSM. XRD ensures the formation of the cubic spinel structure, and the average crystallite size was determined utilizing the Debye Scherer equation, which was found to be lying between 33.10 and 24.11 nm. HR‐SEM images exhibited agglomerated morphology, and the samples were observed to be highly crystalline in nature. EDX spectra confirmed the formation of pure and strontium doped magnesium ferrite, ensuring the existence of all the elements. The bandgap was observed to lie in between 2.02 and 1.57 eV, respectively. TG‐DTA spectra provide information regarding the total weight loss, endothermic, and exothermic transitions. From M‐H loops, it is observed that pure and strontium doped magnesium ferrite exhibits ferromagnetic behavior. Abstract : (i) Sr2+ ion doped magnesiumferrite was synthesized by a microwave combustion method. (ii) Structural, morphological, optical, thermal and magnetic properties are determined for allthe prepared samples. (iii) Hc, Mr and Ms values are measured from the hysteresis loop. Sr2+ ion doped magnesium ferrite nanoparticles exhibitsferromagnetic behaviour.